Aromatic Superhalogens. Issue 16 (18th March 2014) - Child, Brandon Z.; Giri, Santanab; Gronert, Scott; Jena, Puru
Abstract No organic molecules with electron affinities near or above those of halogens are known. We show for the first time that aromaticity rules can be used to design molecules with electron affinities far exceeding those of halogen atoms either by tailoring the ligands of cyclopentadienyl or by multiple benzoannulations of cyclopentadienyl in conjunction with the substitution of CH groups with isoelectronic N atoms. Results based on density functional theory revealed that the electron affinities of some of these organic molecules can reach as high as 5.59 eV, thus opening the door to new class of superhalogens that contain neither a metal nor a halogen atom.